The role of extremist organizations in the formation of negative ideas about Islam - L.B. Mayevs’ka (Українське Pелігієзнавство, 2004)
In the last decade, the activities of various extremist organizations have intensified, which use religious slogans to achieve political goals, sometimes even deliberately distorting the basic tenets of religion. Researchers argue that such organizations put forward some position and then, in order for it to gain weight in the eyes of Muslims, reinforce it with a distorted interpretation of the ayat from the Qur'an or the sayings of the Prophet Muhammad. This is most characteristic of supporters of the extremist trend of Wahhabism. Even during the life of the founder of the current, Muhammad ibn Abd al-Wahhab, theologians of the Muslim holy city of Mecca issued a fatwa (religious conclusion) about the Wahhabis' retreat from the faith because of their beliefs. This conclusion was made by Islamic scholars in connection with the fact that many of the provisions of the teachings of Ibn Abd al-Wahhab contradict Islamic doctrine; Wahhabis also unprovenly accuse Muslims of unbelief, which leads accusers of unbelief. This principle follows from the words of the Prophet Muhammad and is well known among Muslims.